Challenges of New Technology Adoption in Improving Company Growth and Competitiveness - Tajuddin, Imran (Advances in Economics & Financial Studies, 2025)
Purpose: This study examines the challenges and strategies of adopting new technologies to enhance organizational growth and competitiveness in the digital era. It focuses on identifying financial, skill-based, cultural, and external barriers and exploring practical approaches to overcoming them. Research Design and Methodology: A qualitative systematic literature review (SLR) method was employed, synthesizing findings from peer-reviewed articles and academic sources. This approach allowed for a comprehensive analysis of empirical and theoretical perspectives, integrating concepts from innovation diffusion, financial management, and organizational change theories. Findings and Discussion: The study identifies financial constraints, skill gaps, resistance to change, and external factors such as regulatory challenges and inadequate digital infrastructure as critical barriers to technology adoption. It highlights the dynamic interactions among these barriers, revealing how they collectively influence organizational readiness for digital transformation. Strategies such as pilot testing, portfolio diversification, continuous employee training, and regulatory alignment are discussed as essential for overcoming these challenges. The findings also emphasize the role of advanced technologies like Artificial Intelligence (AI), the Internet of Things (IoT), and cloud computing in driving operational efficiency, innovation, and market competitiveness. Implications: The research contributes to academic discourse by offering a holistic framework for understanding technology adoption challenges. Practically, it provides actionable insights for organizations to foster a culture of innovation and align technological initiatives with business goals. Policymakers are urged to invest in digital infrastructure and create supportive regulations to facilitate sustainable digital transformation.